Terminal Ballistics in Ordinary Snow. Small Arms Fire Attenuation - Swinzow, George K (1972)
The terminal ballistics of various types of snow were investigated experimentally and the resulting data have been researched and tabulated. The experimental procedures, especially designed for this purpose, are described and illustrated. It was concluded that snow is an effective protective material, with measurable and significant capability to attenuate small arms fire and neutralize fragment action. A brief discourse was made into the role of snow- covered terrain in combat, its geography and general properties.